The regions of solvability for some three point problem - Sergejeva, Natalija (Mathematical Modelling and Analysis, 2013)
The solvability results are established for the boundary value problem , where x + = max{x, 0}, x - = max{-x, 0}, h is a bounded nonlinearity. The existence results are based of the knowledge of the spectrum for the problem with h ≡ 0.